Ultra-Small, High-Frequency, and Substrate-Immune Microtube Inductors Transformed from 2D to 3D - Yu, Xin (Sci Rep, 2015)
Monolithic on-chip inductors are key passive devices in radio frequency integrated circuits (RFICs). Currently, 70–80% of the on-wafer area of most RFIC chips is occupied by the sprawling planar spiral inductors, and its operation frequency is limited to a few GHz. With continuous scaling of the transistor technology, miniaturization and high frequency operation of inductors have become the bottleneck to meet future demands of wireless communication systems. Here we report on-chip self-rolled-up 3D microtube inductors with extremely small footprint, unprecedented high frequency performance and weak dependence on substrate conductivity. The serpentine metal strips are deposited on an oppositely strained silicon nitrides (SiN(x)) bilayer. After releasing from the sacrificial layer underneath, the metal/SiN(x) layer is scrolled into a 3D hollow tubular structure by the strain induced unidirectional self-rolled-up technology. Compared to the planar spiral inductors with similar inductances and quality (Q) factors, the footprint of tube inductors is reduced by as much as two orders of magnitude, and the frequency at peak Q factor improves more than 5 times on doped substrates. The self-rolled-up 3D nanotechnology platform employed here, that “processes in 2D but functions in 3D”, is positioned to serve as a global solution for extreme RFIC miniaturization with improved performance.